IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 8 TAHUN 2012 TENTANG RETRIBUSI IZIN GANGGUAN DAN KONTRIBUSINYA TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KOTA PEKANBARU TAHUN 2012-2014 - Hadi, Sofyan; ', Ishak (Universitas Riau, 2016)
In the Pekanbaru City Regional Regulation No. 8 of 2012 concerning Disturbance Permits inArticle 3 has been explained that this permit is valid for five (5) years and shall re-register everyyear by paying a levy. But in reality there are many employers who do not pay the levy each year,mainly in the district Charming.The approach used in this study is qualitative and classify informant research include keyinformants, key informants and informant extra. Data collection techniques used in the form ofin-depth interviews and secondary data analysis with qualitative analysis techniques procedure;reduction, data presentation and verification / conclusions.The results showed that the retribution permit interference in Pekanbaru has decreased, eventhough efforts are minor nuisance levels continue developing States at any time for the purposeof investment employers by various businesses. Resistor in retribution disorder is an enumera-tion of objects levy is less good, less than the maximum dissemination and awareness of thepoor to pay the levy.